1998
DOI: 10.1007/bf03401928
|View full text |Cite
|
Sign up to set email alerts
|

No Association between the Serotonin Transporter-Linked Promoter Region Polymorphism and Either Schizophrenia or Density of the Serotonin Transporter in Human Hippocampus

Abstract: Background: Allelic association case-control analysis of a deletion/insertion polymorphism in the serotonin transporter-linked polymorphic region (5-HTTLPR) has suggested associations with unipolar disorder, bipolar disorder, depression, and Alzheimer's disease. Moreover, the heterozygous long form of the 5-HTTLPR has been associated with increased levels of mRNA for the serotonin transporter (5-HTT) and increased serotonin uptake in lymphoblastic cell lines. This study attempts to determine whether there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 16 publications
4
19
0
1
Order By: Relevance
“…21 These results, along with some of the findings from previous human studies, [22][23][24] demonstrate a relationship between the 5-HTTLPR and 5-HT functioning in both human and nonhuman primates (but also see Naylor et al 25 and Jonsson et al 26 ). Although the 5-HTTLPR alleles are differentially active in vitro, relatively few studies have examined direct measures of CNS serotonin function in either humans or other animals.…”
Section: Molecular Psychiatrysupporting
confidence: 51%
“…21 These results, along with some of the findings from previous human studies, [22][23][24] demonstrate a relationship between the 5-HTTLPR and 5-HT functioning in both human and nonhuman primates (but also see Naylor et al 25 and Jonsson et al 26 ). Although the 5-HTTLPR alleles are differentially active in vitro, relatively few studies have examined direct measures of CNS serotonin function in either humans or other animals.…”
Section: Molecular Psychiatrysupporting
confidence: 51%
“…39,41,42,58 Clinical association studies have further examined the relationship between SERTLPR alleles and psychiatric disorders and anxiety-related personality traits, [59][60][61][62][63][64][65][66] suicide, 67,68 alcoholism, 69,70 response to antidepressants [71][72][73] and brain function as revealed by MRI scans. [74][75][76][77] Although many studies have reported correlations between SERTLPR alleles and SERT expression levels or clinical phenotype, almost an equal number of studies have not.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin is reabsorbed after being transported to the neurons and the 5-HTT regulates the degree and duration of serotonin response during this process [3]. Some studies reported alteration of 5-HTT-related findings in patients with schizophrenia: significant increase in the maximum number of 5-HTT sites in schizophrenic patients compared with controls [4], brain region-specific decrease in the density of 5-HTT in schizophrenics [5], significant decrease in the affinity of 3 H-paroxetine binding to the hippocampus [6,7], and decreased number of serotonin uptake sites in the limbic system of schizophrenics [8]; however, a negative finding was also detected [9].…”
Section: Introductionmentioning
confidence: 99%